Data supporting: Microbial community composition of translocated ancient woodland soil: a case study - Hannam, Jacqueline A.; Pawlett, Mark; Borchers, Nicolas (Cranfield University, 2022)
Raw data for study Microbial community composition of translocated ancient woodland soil: a case study. Includes soil pH, organic matter, available N, available P, microbial biomass, microbial activity, PLFA biomarkers
Keywords: ancient woodland'; 'Soil microbiology'; 'Habitat Restoration'; 'Ecology'; 'Soil Biology'; 'Soil Science'; 'Soil Chemistry (excl. Carbon Sequestration Science)'